Teori Islamisasi Kesejahteraan Perspektif Program Riset Sains Islam Lakatosian - m.kholid muslih; nur hadi ihsan; winda roini; Usmanul Khakim (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2020)
This article aims to examine the process of Islamization on the theory of welfare, which is presented by M. Hibatal Azizy in his book “Mendudukkan Kembali Makna Kesejateraan dalam Islam (2014)”. The intended test is carried out through the perspective of the Islamic research program of lakatosian; which is adopted from the Methodology of Scientific Research Programes by Imre Lakatos (w.1974). This research program consists of 4 steps of analysis, namely (1) finding the problem in the initial theory, (2) finding the initial paradigm, (3) shifting of paradigm and (4) building a new theory. Based on this perspective, Azizy has carried out the four steps of the analysis above and produced a welfare theory in accordance with the Islamic paradigm, which called falāh theory of welfare. An important point of his theory is theIslamic welfare includes oriented to the worldly and ukhrowi dimensions. Overall fulfillment of welfare for a Muslim can be specified in 5 aspects of life; religion, soul, reason, descent and wealth.